NEUROPSYCHIATRIC LUPUS – TWO FACES OF ONE DISEASE (TWO CASE REPORTS) - Dimitrijević, Milan; Stojanović, Maja; Mišković, Rada; Kusić, Nataša; Rašković, Sanvila (Srpski medicinski časopis Lekarske komore, 2023)
Introduction: Neuropsychiatric lupus (neuropsychiatric systemic lupus erythematosus – NPSLE) is a form of a systemic autoimmune disease – systemic lupus erythematosus (SLE), with dominant central and peripheral nervous system involvement. Nuclear magnetic resonance imaging (NMRI) of the brain is considered the gold standard for diagnosing patients with NPSLE. Treatment of NPSLE includes the following: high doses of corticosteroids, methylprednisolone pulse therapy, intravenous immunoglobulins, plasmapheresis, immunosuppressants (cyclophosphamide, azathioprine, mycophenolate mofetil), and biological therapy – rituximab. Case reports: In this paper, we present two patients diagnosed with neuropsychiatric lupus, with different clinical manifestations of the disease, as well as the diagnostics performed, and the good clinical outcomes of immunosuppressive therapy achieved in both patients. Conclusion: The pathogenesis of NPSLE involves neuroinflammatory (autoimmune) and ischemic mechanisms. Neuroimaging has shown good results in differentiating patients with SLE from controls. The goal of SLE treatment is to achieve remission or low disease activity and to prevent episodes of exacerbation. Treatment with intravenous cyclophosphamide as well as with systemic corticosteroids has shown significantly positive results in patients with NPSLE. There is great need, in the future, for new biomarkers in the serum and cerebrospinal fluid (CSF), as well as for more innovative radiological procedures. Additional clinical trials that would lead to new therapeutic options for the treatment of NPSLE are necessary.